Instrumen Labelisasi dan Sertifikasi Halal sebagai Perlindungan Hukum terhadap Konsumen Muslim dalam Wacana hukum Ekonomi Islam di Indonesia - Mabarroh Azizah (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The protection of Muslim consumers against halal products is not just halal labeling contained in the Food Law, but must have integrity of other economic laws, so there is guarantee of the implementation of halal labeling. This is closely related to matters of a business nature, such as trade agreements, distribution, advertising, packaging, negligence and misuse of halal labeling. This paper concludes that first, the position of Muslim consumer protection against halal products in Islamic Economic Law has a great attention. Second, the concept of Muslim consumer protection against halal products in Indonesian Economic Law has a strong juridical foundation, that is stated in the 1945 Constitution Article 29 paragraph (1) and (2), which contains about the freedom to implement religious shari'ah. Third, basically the Indonesian Economic Law contains the protection of Muslim consumers against